Analisis Tingkat Pelayanan Terminal Bus Terpadu Pulo Gebang - Soekirman, Atong; Huda, Muhammad Nur; Setyawati, Aswanti; Nurhayati, Siti; Subandi, Subandi (Institut Transportasi dan Logistik Trisakti, 2024)
The main problem is that the DKI Jakarta Provincial Government is still not optimal in carrying out improvements to the Pulo Gebang integrated bus terminal, both in terms of facilities and services. This condition is reflected in the presence of passengers and drivers who have not maximized their use of the Pulo Gebang integrated bus terminal. This study aims to analyze service levels in increasing customer satisfaction. This research uses service quality analysis at the Pulo Gebang integrated bus terminal based on the level of passenger satisfaction using the Service Quality, Importance Performance Analysis and Quality Function Deployment methods. The research sample was bus passengers and the operational implementation unit as well as the Pulo Gebang integrated bus infrastructure and facilities implementation unit, totaling 100 respondents. The calculation results show the suitability value between the average perception score and the lowest average importance score, namely the service attributes, security guarantees and trust in services, which shows that the number of existing buses cannot fulfill customer desires. Other calculation results show that the conformity value does not reach 100%, so the Pulo Gebang Integrated bus terminal has not been able to fulfill customer desires as a whole.